2019
DOI: 10.1136/annrheumdis-2019-216137
|View full text |Cite
|
Sign up to set email alerts
|

Shared decision making in routine clinical care of patients with rheumatoid arthritis: an assessment of audio-recorded consultations

Abstract: ObjectivesAlthough shared decision making (SDM) is advocated in rheumatoid arthritis (RA) treatment, it is largely unclear when, how and to what extent SDM is applied in routine clinical care of patients with RA. This study aimed to investigate the level of SDM in RA treatment from an observer perspective and to assess associations between the level of SDM and characteristics of the clinician, patient and consultation.MethodsThe level of SDM was investigated by scoring audio-recordings of 168 routine consultat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 47 publications
1
25
0
1
Order By: Relevance
“…In addition to the potential time saved by using ePROs, the concept of SDM is an important aspect that could be achieved by continuous patient monitoring and transparent integration of the process into therapy management decisions. A recent study analyzing SDM in RA patients showed that there is still room for improvement [ 32 ]. Interestingly, PROs such as pain, morning stiffness, and patient global assessment were much more often compiled than others, such as SF-36, FACIT-F, or computerized adaptive testing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the potential time saved by using ePROs, the concept of SDM is an important aspect that could be achieved by continuous patient monitoring and transparent integration of the process into therapy management decisions. A recent study analyzing SDM in RA patients showed that there is still room for improvement [ 32 ]. Interestingly, PROs such as pain, morning stiffness, and patient global assessment were much more often compiled than others, such as SF-36, FACIT-F, or computerized adaptive testing.…”
Section: Discussionmentioning
confidence: 99%
“…However, SDM is applied in clinical practice only to a limited extent 8 9. Its low uptake may be attributed to a range of factors affecting successful implementation (eg, a lack of awareness, time constraints and the power imbalance in the healthcare professional–patient relationship) 10 11.…”
Section: Introductionmentioning
confidence: 99%
“…11 In this study 88% of rheumatologists stated that in daily practice they always or very often involved the patient in setting the RA treatment target and the strat- Academic /university 19 (26) Rheumatology nurse in clinic, n (%) 24 (33) shared decision making can be discordant between patient and clinician and in RA a low to moderate level of shared decision making has been identified. 31 This study indicated the need for patient awareness/education of RA-T2T and additionally for the timely use of a disease activity score within the clinical consult. Therefore a KT-tool was developed to address these issues while also prompting a shared decision.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast only 9% of patients were aware of RA‐T2T. Research suggests that the perception of and actual shared decision making can be discordant between patient and clinician and in RA a low to moderate level of shared decision making has been identified 31 …”
Section: Discussionmentioning
confidence: 99%